Failure rather than success : conflict management and resolution in the Democratic Republic of Congo, 1996-1999 - Munyae, Isaac Muinde (Rhodes University, Faculty of Humanities, Department of Political Studies, 2001)
History has proven time and time again that conflict is an inevitable aspect of any given society. The seemingly long-standing nature of conflicts in Africa has been changing over time and these conflicts have been either inter-state or intra-state. However, sometimes intrastate wars have escalated into regional conflicts. These scenarios can be seen in the Great Lakes region of Africa where you have the civil war of 1996-7 and the rebellion, which began in 1998 in the Democratic Republic of Congo (DRC). In the DRC there have been at least four stages of conflict. The first is against the Belgians and secondly, the civil strife of the early 1960s. Third, is the civil strife against Mobutu and fourthly, currently against Kabila. The expanding nature of conflict is characterised by power struggles, politicisation of ethnicity, and the impact of external forces. It is noted that the expanding nature of conflict calls for a change in the methods of conflict management and resolution. Initially conflicts were resolved through military intervention. but with the complexity of African wars it has become apparent that peaceful methods are more prudent. With reference to Africa it can be assumed that conflicts need to be increasingly resolved through political means, such as the use of the diplomatic process. The conflict in Chad between 1968 and 1984 is a good example in which military intervention was used but failed, giving way to mediation and negotiation through the use of diplomacy. Both the DRC and Chadian conflicts are similar because they witnessed the influence of external forces (neighbouring countries and non-African states such as France and the US) and African states attempting to find solutions to their own problems. The conflict in the DRC provides a unique example of the changing nature of intra-state conflict in Africa. Thus, the study aims to trace the characteristics of conflict in the DRC and attempts made at conflict management and resolution. The study uses the period bet ween 1996 and 1999 because it highlights this change in the nature and character of conflict.
Keywords: Conflict management -- Congo (Democratic Republic); Dispute resolution (Law) -- Congo (Democratic Republic).; Congo (Democratic Republic) -- History -- 1997-